TYPES OF WORDS ACCORDING TO THEIR MEANING: SYNONYMS, ANTONYMS AND HOMONYMS (Лучшие интеллектуальные исследования, 2025)
Аbstrаct:  This article investigates the classification of words based on their implications, centering on three essential sorts:  equivalent words, antonyms, and homonyms. Equivalent words are words that share comparative implications and can frequently be utilized traded, whereas antonyms are words with inverse implications, giving differentiate in dialect. Homonyms, on the other hand, are words that sound alike or are spelled alike but have diverse implications. Understanding these sorts upgrades lexicon, improves expression, and makes strides comprehension in both composed and talked communication. This ponder points to clarify each category with cases and highlight their significance in dialect learning and compelling communication.